Clinical evaluation of pit and fissure sealant efficiency in children aged 6-7 - Ivanović Dragan; Marković Dejan; Stojanović Nikola (Serbian Medical Society - Dental Section, Belgrade, 2007)
Introduction: As one of the most important dental diseases, caries cannot be treated with classic therapeutic measures, but very often, there is a need for preventive and prophylactic measures. Aim: The aim of this study was to assess clinical efficiency of composite materials and glass-ionomer cements as pit and fissure sealants in caries prevention. Materials and Methods: The study comprised 50 patients (141 teeth), both sexes, 6-7 years old with at least two erupted first permanent molars. The main diagnostic criterion was smooth enamel surface with no probe faltering on the tooth. Materials tested in this study were two composite materials (Heiloseal-Opak and Helioseal-Transparent) and two glass-ionomers (Fisurit and Fuji VII). For clinical assessment of these materials, modified Cvar-Ryge criteria were used. Results: The obtained results showed no statistically significant differences among materials in respect to retention, marginal adaptation, discoloration and secondary caries. The difference was significant in respect to surface roughness between Fuji VII and Fisurit and Fuji VII and Helioseal-Opak (p<0.05). Conclusion: Composite sealant Heiloseal-Opak and glass-ionomer Fuji VII showed better clinical results in respect to all tested parameters compared to Helioseal-Transparent and Fisurit. .